The Intimate Virtuoso : The Guitar, the Rhetoric of Transformation, and Issues of Spectacle in Music by Fernando Sor, Johann K. Mertz, and Giulio Regondi : a thesis submitted to Massey University and Victoria University of Wellington in partial fulfilment of the degree Master of Music in Classical Guitar Performance, New Zealand School of Music - Garrick, Jamie (Massey University, 2014)
Studies of virtuosity in the eighteenth and nineteenth centuries have tended to focus on the piano and the violin. These instruments were obviously virtuosic and lent themselves to visual and aural displays of power, most notably in the case of Liszt and Paganini. These virtuosi crafted spectacles that were often described with metaphors of power and violence. These spectacles came to characterise the virtuosity of the early nineteenth century. However, the guitar has been largely neglected in scholarship dealing with virtuosity from the late eighteenth and early nineteenth centuries. This is due, in large part, to the status of the guitar within that period. Though popular as an accompanying instrument and in the home, the guitar struggled to find a secure position as a legitimate solo instrument in the public arena. While guitarists such as Dionisio Aguado and Mauro Giuliani were described as ‘virtuosi’, their instrument, unlike the piano and the violin, did not give itself to a spectacle that conveyed notions of power and violence. Rather, the guitar is an intimate instrument, quieter than the piano or the violin, and utilising small movements in the hands. These aspects of the instrument, so often perceived as ‘limitations’ led many writers to dismiss it as an inappropriate instrument for performance in the public spheres occupied by the piano and the violin. Guitarist-composers sought to play to the guitar’s strengths in ways that contrasted with the conventional metaphors of power and violence. Some of these attempts rhetorically aligned the guitar with genres and instruments that carried greater cultural capital. Composers used orchestral metaphors and emphasised the guitar’s ability to imitate other instruments. Other guitarist-composers sought to create a greater spectacle both in and beyond the music itself by emphasising physical movements within the music and writing extra-musical gestures into the music. The rhetoric of transformation was used either by or about the guitarist-composers Fernando Sor, Dionisio Aguado, Johann Kaspar Mertz, and Giulio Regondi, all of whom this exegesis focuses on, demonstrating a desire to legitimise the guitar at a time when it struggled not only to find traction as a ‘serious’ classical instrument, but also a place amongst more obviously virtuosic instruments.
MP4 file of performance recital available with hard copy in the library
Keywords: Sor, Fernando; Aguado y García, Dionisio; Mertz, Johann Kaspar; Regondi, Giulio; Guitar performance; Virtuosity in musical performance; Guitar music; History and criticism; 19th century music